STIGMA DAN KAPITALISASI KEMISKINAN: STUDI KEHIDUPAN SOSIAL KOMUNITAS PENGEMIS DI DESA SEI BULUH KECAMATAN PERBAUNGAN - Ramadhan, Rizki (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
Sosial structure always shows complex categorization. Wealth and poverty are not only seen as the result of functional interactions in society, but rather sosial dialectics that are continuously understood. This article explores the sosial life of the beggar community, especially focusing on the elaboration of the stigma they face from one side of society, and their efforts to capitalize on the situation of poverty as sosial capital, as work that is done routinely to continue life. The research method used here is qualitative with a descriptive approach. Data was taken through observation, interviews and documentation studies. This article finds that beggars in their communities face negative stigma, perceived bias, from the local community and the communities where they operate as beggars. However, on the other hand, these beggars feel immune to their sosial status and understand that the poverty they face must be capitalized on as sosial capital to earn a living. Here, this article puts forward the argument that beggars and their poverty must gain an alternative perspective so that this can be used as additional insight in efforts to understand and resolve the problem of poverty.